Nikolai Wrangell — Researcher of F.S. Rokotov’ Art - Stikhina, Maria I. (Actual Problems of Theory and History of Art, 2013)
In this article we discuss the contribution of Nikolai Wrangell to the studies of the 18th c. Russian painting. He is the author, who “opened” Fyodor Rokotov as a portrait painter. Wrangell recreated for the first time the mysterious image of the painter and gave the scientific interpretation of his art in an article published in the Starye gody magazine (1910). Small article contained original ideas further developed in research by the following generations of art historians. Based on the analysis of articles on Rokotov we attempt to introduce N. Wrangel’s scientific approach, examine the key issues and reveal the evaluation criteria of the portrait painter.
Keywords: N. Wrangell; F. Rokotov; art critic; Silver Age; Russian art of the 18th c; art association Mir iskusstva (“World of Art”); Starye gody (“Old years”) magazine